Pengaruh Store Atmosphere, Shopping Lifestyle, dan Fashion Involvement terhadap Keputusan Pembelian Konsumen Generasi Z pada Produk UNIQLO - Setiawan, Galang Ade (Journal of Indonesian Economic Research, 2024)
This quantitative study aims to analyze the effects of store atmosphere, shopping lifestyle, and fashion involvement on Generation Z consumers' purchasing decisions for UNIQLO products. The study sample comprises 100 consumers aged 17–23 years who have purchased Uniqlo products directly from outlets. Data collection was conducted using a survey method with a questionnaire as the instrument. Instrument testing showed that all question items were valid and reliable. The classic assumption tests indicate that the data is normally distributed, and the regression model is free from multicollinearity and heteroscedasticity. Hypothesis testing using Multiple Linear Regression analysis reveals that: (1) store atmosphere positively and significantly influences purchasing decisions, (2) shopping lifestyle positively and significantly influences purchasing decisions, and (3) fashion involvement positively and significantly influences purchasing decisions. The study findings suggest that a well-crafted store atmosphere enhances consumer purchasing decisions. Additionally, the more resources consumers allocate to obtaining desired clothing, the higher the purchasing decisions are likely to be. Likewise, higher consumer involvement in fashion-related aspects strengthens purchasing decisions. These insights can help companies develop marketing strategies, including optimizing store atmosphere, designing targeted promotions to stimulate a shopping lifestyle, and increasing consumer engagement in fashion-related aspects.